The roles of plant proteases and protease inhibitors in drought response: a review - Moloi, Sellwane Jeanette; Ngara, Rudo (Frontiers in Plant Science, 2023)
Upon exposure to drought, plants undergo complex signal transduction events with concomitant changes in the expression of genes, proteins and metabolites. For example, proteomics studies continue to identify multitudes of drought-responsive proteins with diverse roles in drought adaptation. Among these are protein degradation processes that activate enzymes and signalling peptides, recycle nitrogen sources, and maintain protein turnover and homeostasis under stressful environments. Here, we review the differential expression and functional activities of plant protease and protease inhibitor proteins under drought stress, mainly focusing on comparative studies involving genotypes of contrasting drought phenotypes. We further explore studies of transgenic plants either overexpressing or repressing proteases or their inhibitors under drought conditions and discuss the potential roles of these transgenes in drought response. Overall, the review highlights the integral role of protein degradation during plant survival under water deficits, irrespective of the genotypes’ level of drought resilience. However, drought-sensitive genotypes exhibit higher proteolytic activities, while drought-tolerant genotypes tend to protect proteins from degradation by expressing more protease inhibitors. In addition, transgenic plant biology studies implicate proteases and protease inhibitors in various other physiological functions under drought stress. These include the regulation of stomatal closure, maintenance of relative water content, phytohormonal signalling systems including abscisic acid (ABA) signalling, and the induction of ABA-related stress genes, all of which are essential for maintaining cellular homeostasis under water deficits. Therefore, more validation studies are required to explore the various functions of proteases and their inhibitors under water limitation and their contributions towards drought adaptation.